Determinants of nutritional status of pregnant women attending antenatal care in Western Regional Hospital, Nepal - Lama, Nishant; Lamichhane, Rajendra; K. C., Shreejana; Bhandari, Gia Pun; Wagle, Rajendra Raj (International Journal Of Community Medicine And Public Health, 2018)
Background: Good nutritional status during pregnancy is the precondition for healthy pregnancy outcome. Maternal undernutrition leads to life threatening health consequences to expectant mother and her child. Nepal has considered nutrition as right but still there is discrepancy in nutritional status of pregnant women. Reasons for this are little explored. Thus, the study was carried out to generate evidence on nutritional status of pregnant women and factors influencing it. Methods: A cross sectional descriptive study was carried out using systematic random sampling technique with 282 pregnant women of ≥3rd trimester attending antenatal care in Western Regional Hospital, Pokhara, Kaski, Nepal. Semi-structured questionnaire, 24 hour recall tool, HFIAS measurement tool, MUAC tape and ANC card were used to collect information from participants. Descriptive and statistical analyses were done to summarize the result. Research was adhered to principles of research ethics. Results: Pregnant women having acute malnutrition (MUAC <23 cm) were 24%, low gestational weight gain were 67% and anemic were 12%. Food security, ethnicity and dietary diversity were found to have significant association with the nutritional status of pregnant women. Conclusions: The study generated the evidence on determinants of nutritional status of pregnant women. It has recommended that ensuring household food security, increasing dietary diversity and focusing ethnicity can promote nutritional status of pregnant women.